2007
DOI: 10.1111/j.1365-2664.2007.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking agricultural policies to population trends of Swedish farmland birds in different agricultural regions

Abstract: Summary1. The widespread declines of farmland birds have generally been linked to agricultural intensification. We tested the hypotheses that (i) changes in agricultural policy, through its effects on agricultural intensification and (ii) regional differences in agricultural intensification affect temporal and spatial population trends of farmland birds in Sweden. 2. We analysed regional bird population trends (1976 -2003) for seven common farmland bird species: the migratory lapwing Vanellus vanellus , skyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 40 publications
0
86
2
2
Order By: Relevance
“…Numerous studies on habitat use in migratory farmland birds have shown that fallow is an important habitat during the breeding and winter seasons (e.g., Delgado and Moreira 2000;Silva et al 2004;Wretenberg et al 2007). Whether fallow is also important during the post-fledging period is not known.…”
Section: Communicated By W Lutzmentioning
confidence: 99%
“…Numerous studies on habitat use in migratory farmland birds have shown that fallow is an important habitat during the breeding and winter seasons (e.g., Delgado and Moreira 2000;Silva et al 2004;Wretenberg et al 2007). Whether fallow is also important during the post-fledging period is not known.…”
Section: Communicated By W Lutzmentioning
confidence: 99%
“…This has been caused mainly by a decrease in the diversification of the landscape linked to the elimination of uncultivated areas and agricultural intensification (Smart et al 2000, Orłowski 2005, Donald et al 2006, Wretenberg et al 2007. In contrast, in Eastern Europe, political and economic transformation has often caused the degradation of agriculture and the appearance of a large number of abandoned fields.…”
mentioning
confidence: 99%
“…In southern Sweden traditional farming practices based on animal husbandry and the associated large area of mowed and grazed wet grasslands, which provided habitats for many species, have been turned into intensive cropping systems [22,23]. Today, the remaining wet grasslands are dependent on environmental subsidies to maintain livestock grazing and mowing [24].…”
Section: Introductionmentioning
confidence: 99%